Effectiveness of Self Instructional Model on the Management of Violent Patients among Nursing Personnel in Selected Ward of Lumbini Medical College. - Bandana Pokharel (Journal of Lumbini Medical College, 2013)
Introduction: Mental health nursing is the practice of promoting mental and caring for people with mental illness. Violence towards nurses by the psychiatry patient in clinical setting is an endemic worldwide and a multifaceted problem. Method: Purposive sampling of thirty sample of nurses from psychiatry ward, emergency room and medicine ward were selected. Sampling Technique was pre-experimental, one group pre-test, posttest design, Reliability of the tool (r=0.95) was tested by split half method using Karl Pearson's Product Moment Correlation formula and Spearman-Brown's Prophecy formula. Socio-demographic data by using proforma. Pretest was done, knowledge score was calculated, self-developed instructional model was introduced and after 7 days’ duration post-test was done. Results: Pre-test assessment revealed that the highest percentage (53.34) of the nursing personnel had good level of knowledge. The significance of difference between the pre-test and post-test knowledge scores was statistically tested using paired 't' test and was found to be very highly significant (t=11.66, P < 0.05). Interpretation: The study revealed that there was very highly significant increase in the knowledge following the administration of self-instructional module.